Star-trail artifacts of the advanced-putrefied brain on postmortem CT. (March 2021) - Kobayashi, Tomoya; Yamamori, Moyu; Shiotani, Seiji; Numano, Tomokazu; Ishimori, Yoshiyuki; Abe, Shinji; Hayakawa, Hideyuki
Highlights: Postmortem CT (PMCT) of advanced-putrefied brain with cavitation was performed. PMCT showed numerous star-trail artifacts similar to ring artifacts. Star-trail artifacts do not occur due to mechanical problems. Abstract: We report star-trail artifacts of advanced-putrefied brain on postmortem CT (PMCT) of a 77-year-old male approximately one month after death. After CT calibration, routine PMCT (tube current time product: 400 mAs) showed star-trail artifacts, which arose due to cerebral cavitation, but were hardly visible on low-dose PMCT (100 mAs) due to noise. Low-dose PMCT with 4-time-image summation also showed star-trail artifacts. Those are not due to mechanical X-ray detector problems.